(3eHGOF Mbhb GdEfSGf aj GdESdGe (B:s (3OQGSI ebGQfI aj GdbGfhf GdOhdj GdYGe (B= The principles of human rights in Islam : a comparative study in public international law /s - (3GdaJdGhj, Sgjd MSjf,s 1941- ((3YeGf, GdCQOf (B:s (3OGQ GdKbGaI ddfTQ hGdJhRjY,s, 2014)
(3jJfGhd cJGH (B((3eHGOF Mbhb GdEfSGf aj GdESdGe (B: (3OQGSI ebGQfI aj GdbGfhf GdOhdj GdYGe (B= The principles of human rights in Islam : a comparative study in public international law) (3hGdPj bGe HJCdjag Sgjd MSjf GdaJdGhj aj MhGdj (B(415) (3UaMI ef GdbWY GdeJhSW ehVhY (B((3GdESdGe hMbhb GdEfSGf(B) (3eSJYQVG GdeMJhjGJ GdJGdjI (B: (3GdebOeI, GdHGH GdChd (B: (3Mbhb GdEfSGf GdhWfjI, GdaUd GdChd (B: (3eaghe Mbhb GdEfSGf aj GdESdGe, GdaUd GdKGfj (B: (3Mbhb GdEfSGf GdYGeI, GdaUd GdKGdK (B: (3Mbhb GdEfSGf GdeJYdbI HTNUjJg, GdHGH GdKGfj (B: (3GdMbhb GdSjGSjI hGdGLJeGYjI aj GdESdGe, GdaUd GdChd (B: (3Mbhb GdEfSGf GdSjGSjI aj GdESdGe, GdaUd GdKGfj (B: (3Mbhb GdEfSGf GdGLJeGYjI aj GdESdGe, GdaUd GdKGdK (B: (3GdMQjGJ aj GdESdGe, GdHGH GdKGdK (B: (3Mbhb GdWad hGdeQCI hhGbY Mbhb GdEfSGf aj GdOhd GdESdGejI, Ke jfJgj HGdedGMb hbGFeI GdeUGOQ(B.s
(3HHdjhLQGajI (B: (3UaMI (B397-415.s
Keywords: (3Mbhb GdEfSGf (B((3bGfhf Ohdj(B)s; (3GdESdGe hMbhb GdEfSGfs